Functional changes associated with structural alterations induced by mobilization of a P-element inserted in the Sex-lethal gene of Drosophila. - Salz, H.K.; Cline, T.W.; Schedl, P. (Genetics, 1987)
Genetic analysis of rearrangements within the multifunctional sex determining gene Sex-lethal has allowed correlation of changes in specific functions with DNA alterations. Rearrangements were isolated by mobilization of a P element which is on the 5' side of the gene, at coordinate 0. Previous work has shown that rearrangements associated with alterations in Sxl gene function are found within an 11-kb region between coordinates-11 and 0. Here it is shown that insertion of foreign DNA, per se, at coordinate 0 is compatible with wild-type gene function. However, deletion of sequences on either side of this point generates a mutant phenotype. Deletions extending distally beyond coordinate -6.5 kb result in a null phenotype, whereas smaller distal deletions or proximal deletions eliminate only some Sxl functions.